Stellate Ganglion Block in Anxiety Disorder with Coexistent Resistant Hypertension: A Report - Niraj, G; Charan, N; Mohan, PV Ram; Niraj, S (Archives of Clinical and Medical Case Reports, 2026)
Autonomic nervous system dysfunction is reported in the neurobiology of both anxiety disorder and resistant hypertension. Stellate ganglion block can dampen sympathetic activity and has been effective in the management of treatment-resistant anxiety disorder. Patients with anxiety disorder and coexistent resistant hypertension were reviewed by an interdisciplinary team comprising clinical psychologists, general medicine physicians, and pain medicine and palliative care physicians. Patients were offered stellate ganglion blocks in the management of treatmentresistant anxiety disorder. A validated outcome measure was completed at baseline and post-intervention. Eight patients with anxiety disorder with coexistent resistant hypertension, who underwent stellate ganglion blocks are presented. The intervention resulted in an improvement in anxiety symptoms with enhanced blood pressure control at the 24-week review in seven patients (7/8, 88%). There was a mean reduction of 21 mm Hg in systolic blood pressure and 11 mm Hg in diastolic blood pressure at the 24-week review. All patients were able to reduce antihypertensive medications. Stellate ganglion block could have a role in the management of resistant hypertension with comorbid anxiety.